1981
DOI: 10.1139/f81-126
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Kepone and Mirex in a Model Aquatic Environment: Sediment, Fish, and Diet

Abstract: Laboratory studies of freshwater sediment and a daphnid–bluegill (Daphnia magna–Lepomis macrochirus) food chain indicated that the organochlorine insecticides Kepone and mirex resist microbial degradation, accumulate and resist metabolism in fish, and move through a food chain. We found no direct evidence of degradation of either compound after 56 d of incubation in freshwater sediments under aerobic or anaerobic conditions. Furthermore, we found no metabolism or co-metabolism of 14C-labeled Kepone in sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Aerobic and anaerobic hydrosoils from a small man-made reservoir (Little Dixie, Columbia, MO) and from a tributary of the James River in Virginia (Bailey Creek) contaminated with Kepone were exposed to a single application of [14C] Kepone and [14C]mirex. Details of hydrosoil collection, preparation, and exposure to Kepone and mirex were described by Skaar et al (1981). Sample extracts were purified by using carbon/foam column chromatography, as described by Huckins et al (1978), prior to TLC and EC-GC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Aerobic and anaerobic hydrosoils from a small man-made reservoir (Little Dixie, Columbia, MO) and from a tributary of the James River in Virginia (Bailey Creek) contaminated with Kepone were exposed to a single application of [14C] Kepone and [14C]mirex. Details of hydrosoil collection, preparation, and exposure to Kepone and mirex were described by Skaar et al (1981). Sample extracts were purified by using carbon/foam column chromatography, as described by Huckins et al (1978), prior to TLC and EC-GC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments by Reinert (1972) On dieldrin showed that daphnia and guppies accumulated more from water than from food exposed to similar COncentrations in water. Skaar et al (1981) using bluegills feeding On daphnids found that they accumulated < 7% of their load of kepone and mirex from food. Canton et al (1975) investigated the chlorella-daphnia-lebistes food chain transfer of HCH and concluded that transfer from water was the most important but food was a significant source.…”
Section: E Operation Of Biomagnification and Bioconcentration In Aqumentioning
confidence: 99%